2007
DOI: 10.3390/i8070695
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of a Series of FluorinatedPyrano-nucleoside Analogues of N4-benzoyl Cytosine andN6-benzoyl Adenine

Abstract: Fluorinated nucleoside analogues are known as antitumor, antiviral and chemotherapeutic agents, although the antioxidant activity of this kind of molecules is not yet investigated. In this study we have tested the antioxidant activity of a series of modified pyrano-nucleoside analogues using three in vitro assays. Firstly, the antioxidant capacity of the products was assessed using the DPPH assay and secondly, in order to examine the ability of the products to protect DNA from the activity of reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Method described by (Spanou, Manta, Komiotis, Dervishi, & Kouretas, 2007)was used with some modifications. 3 ml of 0.1 mM 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) in methanol was added to 250 ll of extract.…”
Section: Free Radical Scavenging Activity (Frsa%)mentioning
confidence: 99%
“…Method described by (Spanou, Manta, Komiotis, Dervishi, & Kouretas, 2007)was used with some modifications. 3 ml of 0.1 mM 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) in methanol was added to 250 ll of extract.…”
Section: Free Radical Scavenging Activity (Frsa%)mentioning
confidence: 99%
“…Lately, nucleosides bearing a six-membered carbohydrate moiety have been evaluated for their potential antiviral [9 -11], antioxidant [12], and antibiotic [13] properties and as building blocks in nucleic acid synthesis [14,15]. Insertion of an unsaturation in the 29,39-position of the sugar moiety of the aforementioned nucleosides, distinguishes this ring system from common six-membered rings [16] and allows to categorize the cyclohexene ring as a bioisoster of a saturated furanose ring.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, nucleosides containing pyranosyl rings have been synthesized along with their analogs in order to develop antitumor, 7,8 antiviral, [9][10][11][12][13] antioxidant, 14 and antimicrobial reagents. 15 Experimental data also revealed that human poly(A)-specific ribonuclease 16 and glycogen phosphorylase 17 are among the molecular targets of these compounds.…”
Section: Introductionmentioning
confidence: 99%